Management of gallbladder empyema in a patient with situs inversus, levocardia and morbid obesity: a case report - Oliveira, Dulcyane Ferreira de; Pinho, Denis Alves; Rodrigues, Fernando Fernandes; Marques, Luiz Fabrício Moura; Araújo, Pedro Henrique Rosa; Pinheiro, Reginaldo Conrado; Rodrigues, Yomara Jesuina Lins (Brazilian Journal of Case Reports, 2021)
Situs Inversus with levocardia is an unusual condition, in which the main organs of the thorax and abdomen are located in a reverse or enantiomorphic position in relation to the usual topography. It is estimated a prevalence of 1:10000 people with some Situs Inversus condition, but Situs Inversus with Levocardia is reported in only 1:22000 cases. The presence of acute cholecystitis in patients is an extremely rare event,however, one of its possible complications, Gallbladder Empyema can develop, causing an increase in severity and the need for surgical intervention. Since the inversion of abdominal organs proper to Situs Inversus with levocardia is commonly associated with the transposition of great vessels, fatally, as described in the literature of Vesicle empyema and Situs Inversus, it only occurred in patients with dextrocardia, not yet being reported in patients with Levocardia. We report a case of a female patient with pain in the left hypochondrium with Situs Inversus Viscerum, Levocardia, Empyema of Biliary Vesicles and Morbid Obesity.